The contribution of learning motivation and self-confidence towards the resolution of students'learning problems - Annisa Aulia; Marjohan Marjohan; Rakimahwati Rakimahwati (Universitas Negeri Padang, 2019)
Students' ability to solve learning problems is influenced by the factors of learning motivation and self-confidence. Students who are able to solve problems in learning will be able to get satisfying results. Students who are unable to solve problems in learning will experience failure in achieving a goal. This study aims at looking at the contribution of learning motivation and self-confidence to the ability to solve the problem of student learning at SMAN 1 Lintau Buo. This type of research was quantitative with correlational methods. The sample of this research was the students of class X and X1 of SMAN 1 Lintau Buo identified from the AUM PTSDL results having the most problems. The research instrument used a learning motivastions, self confidence and the resolution of students learning problems. The result of the reliability test of the learning problem-solving ability was 0.759. The research data were analyzed by using multiple regressions. The research findings showed that: learning motivation, in general, was in the high category. The students’self-confidence was generally in the high category. The students' problem-solving abilities were generally in the high category. The learning motivation contributed positively and significantly to the learning problem-solving abilities. The self-confidence contributed positively and significantly to students' learning problem-solving abilities, and the learning motivation and self-confidence together contributed positively and significantly to the students' learning problem understanding abilities.